The STEM Selfing Process: Nondigital and Digital Determinants of Aspirational STEM Futures. (June 2020) - Robinson, Laura
This article takes a fresh approach to analyzing the nondigital and digital sources of STEM (science, technology, engineering, and math) intent among low–socioeconomic status (SES) high school students attending a Title I public high school in agricultural California. Through a hybrid quantitative–qualitative analysis of data, STEM intent is examined vis-à-vis the selfing process. STEM intent is conceptualized as the product of identity work that can be supported by digital engagements of diverse types. STEM identity is built and reinforced by exposure to digital resources at home, aspirations related to computer programming, and digital activities, particularly programming and/or gaming for at least one hour per week. The linkages are demonstrated quantitatively through logistic regression models and qualitatively with excerpts from in-depth interviews with matched STEM intent students. The regression models show that both nondigital factors and digital engagements influence the odds of expressing STEM intent among high school seniors. As the qualitative analysis demonstrates, these determinants are intimately linked to identity work in which STEM intent students imagine themselves as creators in STEM fields. Digital engagements such as programming, gaming, and internet exposure all play a crucial part in the STEM selfing process in which students imagine their future STEM selves by bringing to life the role of STEM creator. In the article's concluding discussion these findings are developed in a new theoretical direction as evidence for the agentic technological self.